PENGEMBANGAN RPP INTERAKTIF BERBASIS PERMAINAN EDUKATIF KARTU IRAMA UNTUK MENINGKATKAN RITME DAN KERJA SAMA SISWA KELAS V SDI BEIPOSO - Maria Lidya Fenansia Ua Soa; Yeremias Talo; Vincencio Appaulo Rivaldo Bata (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to describe the development of an interactive lesson plan (RPP) based on educational games for music arts instruction at Beiposo Elementary School. The study used a qualitative descriptive approach, with teachers at Beiposo Elementary School as subjects. Data were collected through observation, interviews, and documentation studies. The results indicate that music arts instruction has not been optimal because the lesson plan has not been designed interactively and the learning still focuses on introduction to the material. As a result, students experience difficulties in understanding rhythm, tempo, and musical notation. The development of an interactive lesson plan based on educational games is considered to help create more active and enjoyable learning, as well as improve students' understanding of rhythm and teamwork.